Pregnancy complicated by abdominopelvic hydatid disease - Tyagi, Shakun (BMJ Case Rep, 2012)
A 22-year-old second gravida presented with asymptomatic abdominal and pelvic hydatid disease at 16 weeks gestation. She opted for conservative management and was treated with oral Albendazole. She underwent elective caesarean along with cyst excision at term as the large pelvic cyst precluded vaginal delivery. A healthy baby girl weighing 2600 g with Apgar of 9, 9 at 1 and 5 min was delivered.